Hate speech in the comment column of abidzar al ghifari’s instagram post: A pragmatic approach - Zahara, Fanni; Hidayati (Humanities & Language: International Journal of Linguistics, Humanities, and Education, 2025)
Hate speech is a phenomenon that frequently occurs in society, particularly on social media. Hate speech refers to sentences designed to contain harsh words to insult, hate, and discriminate against the characteristics, race, religion, and even the gender of a person or group of people. This study aims to examine the types of hate speech contained in the comment column of Abidzar Al Ghifari's Instagram post using the types of hate speech based on the National Police Chief's circular letter number SE/6/X/2015. The researcher also revealed the illocutionary act of the hate speech using Speech Act Theory by Searle (1969). The qualitative method was used to describe this research. Data were collected from the comment column on Abidzar's Instagram posts. The data were analyzed using data analysis procedure techniques by Miles and Huberman (2014). The results showed that there were 30 hate speeches with each type, namely, insult (10 data), defamation (5), provocation (11), and incitement (4).  As for the illocutionary act data, there are (4) assertive data, (17) directive data, (3) commissive data, and (6) expressive data. It can be seen that the most dominant type of hate speech is provocation, and for an illocutionary act, it is directive.